2022
DOI: 10.1680/jencm.18.00028
|View full text |Cite
|
Sign up to set email alerts
|

Overview of large-eddy simulation for wind loading on slender structures

Abstract: Understanding and predicting the effects of wind loading on a structure is necessary for a safe, effective, and economical engineering design. Wind tunnel techniques are expensive and often provide data that is not sufficiently detailed for the structural engineer. With increasing advances in computational capabilities, it has recently become feasible to investigate these flows using numerical techniques. Of these, one of the most effective approaches to simulate the turbulence observed in natural wind is Larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 113 publications
2
5
0
Order By: Relevance
“…Overal, the small scale FST (i.e., ILS/D ≤ 1) has little impact on the lift PSD for the forced oscillating cylinder. This is consisten with those for a rectangular cylinder in small scale FST [18,19], in which they concluded that the FST evidently reduced the response. Miyazaki and Miyata [5] and Tamura and Ono [17] studied the response of a square cylinder in the FST with larger integral length scales (1.5 ≤ ILS/D ≤ 2), found only in a small range of the Scruton number 20 ≤ Sc ≤ 30 the amptitude of the response was evedently increased.…”
Section: Fluctuating Lift and Its Power Spectrum Distributionsupporting
confidence: 56%
See 2 more Smart Citations
“…Overal, the small scale FST (i.e., ILS/D ≤ 1) has little impact on the lift PSD for the forced oscillating cylinder. This is consisten with those for a rectangular cylinder in small scale FST [18,19], in which they concluded that the FST evidently reduced the response. Miyazaki and Miyata [5] and Tamura and Ono [17] studied the response of a square cylinder in the FST with larger integral length scales (1.5 ≤ ILS/D ≤ 2), found only in a small range of the Scruton number 20 ≤ Sc ≤ 30 the amptitude of the response was evedently increased.…”
Section: Fluctuating Lift and Its Power Spectrum Distributionsupporting
confidence: 56%
“…The pioneering studies of non-stationary winds or oscillating bluff bodies usually considered smooth inflow only, e.g., [5,[15][16][17]. Only a small number of published papers studied aerodynamics of oscillating square or rectangular cylinders in freestream turbulence, e.g., [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lift coefficient of the two free-stream turbulence cases is reduced by an average of 22 % within 15 • ↓≤ 𝛼 ≤ 22 • ↓. The reason for the reduction of lift at pre-stall and during the early stages of downstroke is due to the impingement of the incoming large-scale turbulence on the LEVs and the subsequent disordered LEVs (see Daniels & Xie 2022). One mechanism is the freestream large-scale turbulence entrainment -the process by which mass is transferred from the external flow regime to the LEV regime (see figure 6b-d (middle) and (right)).…”
Section: Effect On Aerodynamic Characteristics Formentioning
confidence: 99%
“…Jacome et al [12] optimized the aerodynamic-induced vibration of the wing based on the uncertainty-based aerodynamic optimization method. Scholars at home and abroad have also carried out related research on steel structures [13], high-rise buildings [14][15][16] and other building structures [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%